2022
DOI: 10.1111/1756-185x.14375
|View full text |Cite
|
Sign up to set email alerts
|

Risk of incident type 2 diabetes in patients with psoriatic arthritis: A systematic review and meta‐analysis of cohort studies

Abstract: Psoriatic arthritis (PsA) is a chronic multisystem inflammatory disease which affects 10%-40% of psoriasis patients. [1][2][3] Many lines of evidence indicate that patients with PsA have a greater risk of cardiovascular morbidity and mortality, mainly linked to systemic inflammation, medications, traditional cardiovascular risk factors as well. 4-6 Among these risk factors, diabetes is a major risk factor for cardiovascular diseases in the general population 7 and the presence of diabetes in PsA significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Several studies have shown that patients with PsD are at increased risk of diabetes ( 4 ). In a systematic review and meta-analysis of cohort studies, the incidence of type 2 diabetes was 13.4 and 7.8/1000 patient-years in patients with PsA and non-rheumatic control subjects, respectively ( 29 ). In a systematic review of CV comorbidities in PsA, the prevalence of diabetes was found to be increased in patients with PsA compared with controls ( 30 ).…”
Section: Cardiometabolic Comorbidities In Psdmentioning
confidence: 99%
“…Several studies have shown that patients with PsD are at increased risk of diabetes ( 4 ). In a systematic review and meta-analysis of cohort studies, the incidence of type 2 diabetes was 13.4 and 7.8/1000 patient-years in patients with PsA and non-rheumatic control subjects, respectively ( 29 ). In a systematic review of CV comorbidities in PsA, the prevalence of diabetes was found to be increased in patients with PsA compared with controls ( 30 ).…”
Section: Cardiometabolic Comorbidities In Psdmentioning
confidence: 99%
“…Conventional systemic treatments have been associated with an increased risk of major adverse cardiovascular events 11 ; however, targeted therapies have not shown an association 12 . Although defects in glucose metabolism among patients with psoriatic disease are not clearly established in previous studies, epidemiological studies suggest an association between type 2 diabetes and psoriatic disease 13 , 14 .…”
Section: Introductionmentioning
confidence: 86%
“…In a meta-analysis of 44 observational studies, the pooled OR was determined to be 1.76 (95% CI 1.59–1.96), with the highest risk for patients with PsA (OR 2.18, 95% CI 1.36–3.50) and in those with severe psoriasis [ 17 ]. In addition, another meta-analysis of five cohort studies found a 38% increase in the risk of diabetes among patients with PsA, with an incidence rate of 13.4 per 1000 patient-years [ 18 ]. Furthermore, an atherogenic lipid profile was reported among patients with psoriasis, compared to patients without psoriasis.…”
Section: Epidemiology Data Supporting the Association Between Psorias...mentioning
confidence: 99%